Leadership and Communication Dynamics in Digital Project Teams: Exploring Their Influence on Team Performance - Astuti Widiati; Jati Wahyono Agustinus; Erina Sovania; Carolina Ovriane Rahang; Clara Yusta Cantika (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
By developing practical skills which fit industry requirements, teamwork is promoted as it enhances all-round team performance. Project-based learning provides practice for cultivation of these skills, teamwork is the pivotal factor. This study measures how well students have developed their teamwork concepts through project-based courses that are student-oriented in terms of understanding individual roles and group work. A Structural Equation Model based on Partial Least Squares (SEM-PLS) was used to evaluate the team member interaction in the project related team working at Universitas Tarakanita. The findings confirm that effective teamwork is based on open line of communication, clearly defined assignments and respect for individual skill. Shared objectives as well as organized conflict resolution procedures also contribute to the effectiveness of the team. The study took place at the Universitas Tarakanita from 18 March to 21 May 2025 with approximately 100 students. Upon completion of the project, students answered questionnaires on their experience. These findings offer educators and learners practical approaches to assembling and leading successful teams in the project-based classes. The research also notes the relevance of integrating reflective practices in these courses for the development of teamwork skills in students. Re-evaluating our own contributions as we work in groups as well as reviewing the teamwork that supports our peers, makes students more self-aware and helps them to improve. The study suggests that reflective practices on the creative environment and informal leadership should be more structured and makes the case that peer feedback will make a significant difference in how teams collaborate. Taken together, these approaches get students to articulate better, solve problems better, and are a great preparation for jobs that are adapted to and collaborative with others. It should be followed up with studies to investigate the effectiveness of implementation strategies on graduates’ performance in the workplace over time.